2013
DOI: 10.1017/s1355617713000039
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Social Cognition and Pragmatic Language in Adolescents with Traumatic Brain Injuries

Abstract: Traumatic brain injuries (TBI) in children and adolescents can impair social cognition and communication skills but there are few assessment tools suitable for adolescents. The Awareness of Social Inference Test (TASIT) uses professionally enacted audiovisual vignettes of everyday conversational exchanges and is a valid measure of social perception disorders in adults. This study examined its utility for assessing impairments in social cognition in a group of 16 adolescents with TBI, compared to a group of 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 56 publications
(58 reference statements)
2
30
0
Order By: Relevance
“…13,15,16,62,80 Considering the interplay between both domains, the current findings support findings suggesting that communication impairments are associated with poor social outcomes. 16,46,56,57 The current results provide a preliminary insight into the very long-term outcomes in high-level language and social outcomes, as well as the interplay between these 2 domains for individuals who are several decades postinjury and provide an important extension of previous findings (up to 14 years post-childhood TBI 16,18,62,69 or only presented evidence based on 1 case 50 years postinjury 19 ). Hence, this present report on outcomes on average 31 years postinjury is filling an important gap in the previously available literature on long-term language and social outcomes post-childhood TBI.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…13,15,16,62,80 Considering the interplay between both domains, the current findings support findings suggesting that communication impairments are associated with poor social outcomes. 16,46,56,57 The current results provide a preliminary insight into the very long-term outcomes in high-level language and social outcomes, as well as the interplay between these 2 domains for individuals who are several decades postinjury and provide an important extension of previous findings (up to 14 years post-childhood TBI 16,18,62,69 or only presented evidence based on 1 case 50 years postinjury 19 ). Hence, this present report on outcomes on average 31 years postinjury is filling an important gap in the previously available literature on long-term language and social outcomes post-childhood TBI.…”
Section: Discussionsupporting
confidence: 56%
“…44,45 Relying on frontal lobe input to relay neural processes, these complex language functions are required for deciphering nonliteral meanings, which allow social messages to be enriched by inferential and humorous expressions. 12,[46][47][48] These later emerging higher-order cognitive-linguistic skills are important for academic progress, development of peer relationships, socioemotional well-being, and vocational success. [49][50][51][52][53][54] Later developing high-level language skills depend on the maturity of linguistic skills as well as on the maturity of a range of cognitive skills that support language, such as executive function and working memory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well recognised that outcomes vary between people with ABI, but also that individuals may fluctuate in their capacity depending on the expectations and demands being placed upon them at any given time and environment. Within the wider literature, it has been suggested that the full realisation of a person's functional capacity does not become evident until early adulthood, when expectations for higher level executive functioning are increased (McDonald et al, 2013).…”
Section: Individual Characteristics Related To Abimentioning
confidence: 99%
“…McDonald and colleagues (2013) reported that people with ABI often experience difficulty with pragmatic communication, whereby they have difficulty organising and maintaining topics of conversation. These difficulties can result in rejection by peers which further isolates them and limits their ability to practise and develop these skills (Bellon & Rees, 2006;McDonald et al, 2013). …”
Section: Community Contextmentioning
confidence: 99%